Serum concentrations of IL-1β, IL-6, and TNF-α in dogs with chronic kidney disease in uremic syndrome undergoing intermittent hemodialysis with and without bypass - Maia, Suellen Rodrigues [UNESP]; Picelli de Azevedo, Maria Gabriela [UNESP]; Geraldes, Silvano Salgueiro [UNESP]; de Moraes, Reiner Silveira [UNESP]; Okamoto, Adriano Sakai [UNESP]; Melchert, Alessandra [UNESP]; Takahira, Regina Kiomi [UNESP]; Ferreira, João Carlos Pinheiro [UNESP]; García, Henry David Mogollón; Okamoto, Priscylla Tatiana Chalfun Guimarães [UNESP] (Taylor & Francis, 2024)
Intermittent hemodialysis (IH) is an important therapy in the context of kidney dysfunction in dogs. However, its impact on pro-inflammatory cytokines is unclear. This study assessed IL-1β, IL-6, and TNF-α serum concentrations in dogs with chronic kidney disease (CKD) undergoing one session of IH without bypass (IH group, n = 4) and with bypass (IH + bypass group, n = 4). The control group (CG) included four healthy dogs. Cytokine levels were measured before, during, and after the first IH session. Comparative analyses of each cytokine within each group and time point were performed, along with a global comparison between groups. No significant changes were observed in cytokines across evaluation times in the IH groups. IL-1β was significantly higher post-session in the IH and IH + bypass groups compared to CG. Globally, IL-1β and TNF-α concentrations were significantly higher in the IH (11.41 pg/mL (10–16.17) and 2 pg/mL (2–88.54), respectively) and IH + bypass groups (10 pg/mL (10–10) and 2 pg/mL (2–215.5), respectively) compared to CG (0.96 pg/mL (0–3.56) and 0 pg/mL (0–0.003), respectively). The IH group also showed elevated IL-6 concentration (0.1 ng/mL (0.1–0.5)) compared to CG (0 ng/mL (0–0.1)). Higher IL-1β and IL-6 concentrations were observed in the IH group (11.41 pg/mL (10–16.17) and 0.1 ng/mL (0.1–0.1), respectively) compared to the IH + bypass group (10 pg/mL (10–10) and 0.1 ng/mL (0.1–0.5), respectively). In conclusion, a single IH session, with or without bypass, did not increase pro-inflammatory cytokines in CKD dogs with uremic syndrome but maintained the inflammatory state. Dogs undergoing IH without bypass may receive a stronger stimulus for cytokine release.
Keywords: cytokines; Dogs; hemodialysis; inflammation; kidney dysfunction